Willingness to pay for waste management improvement in Dhaka city, Bangladesh - Afroz, Rafia; Hanaki, Keisuke; Hasegawa-Kurisu, Kiyo (Elsevier, Inc., 2009)
We employed the contingent valuation method to estimate the willingness to pay of the respondents to improve the waste collection system in Dhaka city, Bangladesh. Our objective was to estimate how WTP differs between respondents who received or did not receive door to door waste collection. The methodology consisted of asking people directly about their willingness to pay an additional waste collection service charge to cover the costs of a new waste management project. The mean value of WTP for areas that received waste collection service areas was higher than for residents of areas that did not but the difference was not statistically significant. The aggregate value of WTP of the respondents in Dhaka city was 7.6 million Taka (USD0.1 million).